2014
DOI: 10.35792/zot.34.0.2014.4791
|View full text |Cite
|
Sign up to set email alerts
|

Produksi Dan Kandungan Protein Maggot (Hermetia Illucens) Dengan Menggunakan Media Tumbuh Berbeda

Abstract: PRODUCTION AND PROTEIN CONTENT OF MAGGOT (HERMETIA ILLUCENS)USING DIFFERENT GROWTH MEDIA. Mandar bird (Gallirallus) called “weris” bird in North Sulawesi, had been generally known in Minahasa and Kotamobagu areas. Bird in the family of the Rallidae have a small to medium body size. The purpose of this study was to obtain the morphometric characteristics of weris birds in the areas of Kotamobagu. The expected benefit of this study was to provide information about morphometric charaeteristics of weris birds, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
19

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 0 publications
2
14
0
19
Order By: Relevance
“…Pondok pesantren merupakan pusat pembelajaran bagi generasi muda di Indonesia sejak dahulu. Kemenag (2019) Katayane et al (2014) komponen terbesar yang mempengaruhi keberhasilan dalam kegiatan usaha peternakan ialah pakan ternak (50-70%). Hampir semua bahan pakan unggas masih impor diantaranya tepung ikan, bungkil kedelai, leguminosa dan tepung darah.…”
Section: Pendahuluanunclassified
“…Pondok pesantren merupakan pusat pembelajaran bagi generasi muda di Indonesia sejak dahulu. Kemenag (2019) Katayane et al (2014) komponen terbesar yang mempengaruhi keberhasilan dalam kegiatan usaha peternakan ialah pakan ternak (50-70%). Hampir semua bahan pakan unggas masih impor diantaranya tepung ikan, bungkil kedelai, leguminosa dan tepung darah.…”
Section: Pendahuluanunclassified
“…The results of research from several previous researchers who used palm kernel cake media showed that the biomass produced from this study was much higher. Silmina et al at natural culture produced 25-50gram biomass [16]; Fahmi et al resulted in 1kg/3kg BIS media [17]; Obtained a density of 1.21 maggot larvae/cm 3 with an average weight of 150 grams, in other media, 2kg coconut cake, Katayane et al produced fresh weight of maggot 93.42 grams through 0.45 grams of egg stocking [18].…”
Section: A Maggot Productionmentioning
confidence: 99%
“…Tingkat mortalitas yang terjadi berkisar antara 2,4%-12,8% atau sekitar 12-64 ekor larva yang mati selama 14 hari diberi perlakuan. Perbedaan ini diduga disebabkan adanya perbedaan suhu dan kelembaban masing-masing media maupun nutrisi yang terkandung dalam media yang berpengaruh pada pertumbuhan maupun perkembangan (Katayane, 2014).…”
Section: Tingkat Mortalitas Larvaunclassified